2022
DOI: 10.13164/mendel.2022.1.001
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Incremental Learning Algorithm for Diagnosing COVID-19 from Chest X-ray Images

Abstract: The new Coronavirus or simply Covid-19 causes an acute deadly disease. It has spread rapidly across the world, which has caused serious consequences for health professionals and researchers. This is due to many reasons including the lack of vaccine, shortage of testing kits and resources. Therefore, the main purpose of this study is to present an inexpensive alternative diagnostic tool for the detection of Covid-19 infection by using chest radiographs and Deep Convolutional Neural Network (DCNN) technique. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…After passing through these two convolutional layers, the feature map is reduced to a smaller size of around 16, eliminating the need for further locality modeling and invariance removal. The authors in [1] have suggested that a 99 frequency-time filter for the first convolutional layer and a 43 frequency-time filter for the second convolutional layer are enough to cover the entire frequencytime space, hence these filter sizes are employed for the first and second convolutional layers, respectively.…”
Section: Architecture Of Hybrid Bilstm-cnns For Voice Pathology Detec...mentioning
confidence: 99%
See 1 more Smart Citation
“…After passing through these two convolutional layers, the feature map is reduced to a smaller size of around 16, eliminating the need for further locality modeling and invariance removal. The authors in [1] have suggested that a 99 frequency-time filter for the first convolutional layer and a 43 frequency-time filter for the second convolutional layer are enough to cover the entire frequencytime space, hence these filter sizes are employed for the first and second convolutional layers, respectively.…”
Section: Architecture Of Hybrid Bilstm-cnns For Voice Pathology Detec...mentioning
confidence: 99%
“…The suitable number of layers in an hybrid BiLSTM network and CNNs [1] for voice pathology detection depends on several factors, including the complexity of the data, the size of the dataset, and the computational resources available. In general, a deeper network can capture more complex patterns and features in the data, which can lead to better performance in terms of accuracy.…”
Section: Architecture Of Hybrid Bilstm-cnns For Voice Pathology Detec...mentioning
confidence: 99%
“…Smart health systems can assist doctors in handling patient complaints [28,15,51,52,48,4,6] by providing accurate recommendations [3,9,37,30,13,44]. The Case-Based Reasoning (CBR) model is a model that is widely used in the health sector [21,46,40,36,14,50], but has lower performance than the performance of modified CBR models [1,45].…”
Section: Introductionmentioning
confidence: 99%
“…learning techniques have been developed with multiple applications in the world. For example, in the climate [28], food industry [18], and health [2,3], among others. They correspond to data analysis techniques that provide computers the ability to learn from experience without relying on a given equation as a model.…”
Section: Introductionmentioning
confidence: 99%